1.34 billion-year-old magmatism on Mars evaluated from the co-genetic nakhlite and chassignite meteorites. (1st October 2018) - Udry, Arya; Day, James M.D.
Abstract: Nakhlite and chassignite martian meteorites have similar crystallization (1340 ± 40 Ma) and ejection (∼11 Ma) ages, and 87 Rb- 87 Sr and 143 Sm- 144 Nd compositions. Using a near-comprehensive suite of these rocks, we place further constraints on nakhlite and chassignite petrogenesis, utilizing bulk rock and mineral major- and trace-element compositions, and quantitative textural data for 17 samples, including three recent finds (Northwest Africa [NWA] 10153, NWA 10645, and NWA 11013). Bulk rock and mineral compositions indicate that nakhlites and chassignites originated from <5% partial melting of a highly depleted source, in the presence of residual garnet. Significant fractionation of olivine and pyroxene from parental magmas led to formation of cumulate dunites (chassignites), and augite-rich cumulates with relatively low abundances of interstitial material (nakhlites). We show that two nakhlite groups exist with high and low absolute trace-element abundances, which are consistent with groupings from previous studies based on mesostasis content and volatile element contents. The discrepancy between the parental melt and cumulate bulk rock compositions indicates that a missing fractionated melt composition complementary to nakhlites and chassignites should exist on Mars. Quantitative textural analyses of both nakhlites and chassignites are consistent with emplacement as distinct lava flows and/or magmatic bodies close to the martian surface, rather than from a single sill or lava flow sequence. Although originating from the same parental melt to nakhlites, chassignites likely represent cumulates that were either erupted as xenoliths, or occurred as crystal settling pods within dikes or sills and thus represent a different batch of flow/magma from the nakhlites. Determination of an ancient 207 Pb- 206 Pb age (3.95 ± 0.16 Ga) for an apatite grain in NWA 998 is consistent with hydrothermal alteration of nakhlites by ancient crustal-derived fluids immediately following their emplacement. We interpret the apatite age, which is highly distinct from the crystallization age of nakhlites, to indicate addition of Cl-rich fluids driven by hydrothermal circulation of martian crustal brines during emplacement of the nakhlites and chassignites. Although the spatial location of nakhlites and chassignites at the martian surface remains unconstrained, our results indicate similar emplacement features to those observed in terrestrial volcano-magmatic systems.